Effect of Financial Distress, Auditor Quality, and Tenure on Going Concern Audit Opinion with Opinion Shopping as Moderating Factor - Ahmad Jarot; S. Suhendar; Sania Nuraziza (Manunggal Halim Jaya, 2026)
This study aims to examine the effect of financial distress, auditor quality, and auditor-client tenure on going concern audit opinion, with opinion shopping as a moderating variable. This research is motivated by the inconsistency of previous findings and the need to explore managerial opportunism through auditor switching behavior. The study population comprises companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The sample selection was conducted using purposive sampling, resulting in 10 companies with 50 firm-year observations. The data were analyzed using Moderated Regression Analysis (MRA). The results indicate that financial distress, auditor quality, and auditor-client tenure have a significant impact on the going concern audit opinion. Additionally, opinion shopping significantly moderates the effect of auditor quality and auditor-client tenure on going concern opinion, but does not moderate the effect of financial distress. This study contributes to the literature by integrating opinion shopping as a moderating variable, an approach that remains underexplored, particularly in the consumer goods sector. Practical implications include reinforcing auditor independence and rotation policies to mitigate audit bias.